Is There a Relationship Between Obstructive Sleep Apnea (OSA) and Hearing Loss? - Ekin, Selami (Med Sci Monit, 2016)
BACKGROUND: Obstructive sleep apnea (OSA) is a common disorder with an estimated prevalence in the general population of 2–5%. Its main clinical features are loud snoring and breathing stoppage during sleep. Ischemia could be a consequence of noise-induced hearing loss because cochlear oxygen tension is reduced during and after noise exposure. In this study, we evaluated auditory function in patients affected by OSA and simple snoring. MATERIAL/METHODS: A total of 66 participants (male to female ratio: 40:26) were included in the study, of which 21 were in the control group, 18 were in the simple snoring group, and 27 were in the OSA patient group. Polysomnography and audiometric examination were performed in all participants. RESULTS: The mean ages of the participants in the control, simple snoring, and OSA groups were 39.14±9.9, 37.28±8.2, and 41.56±8.99 years, respectively. There were no statistically significant differences among groups regarding age or sex; however, there were statistically significant differences among groups in body mass index, apnea-hypopnea index scores, mean saturation, and duration under 90% saturation. In addition, statistically significant differences were found between the patient group and the control and simple snoring groups concerning the mean saturation, duration under 90% saturation, and the extended high frequency of hearing. CONCLUSIONS: These data show that snoring may cause hearing loss at extended high frequencies.